Review on the design modifications of a solar air heater for improvement in the thermal performance. (June 2020) - Arunkumar, H.S.; Vasudeva Karanth, K.; Kumar, Shiva
Abstract: Solar air heaters are widely used in various household and industrial applications. Reduced thermal efficiency of solar air heaters has necessitated the researchers to focus on the improvement of the thermal performance by providing artificial flow modification techniques in the flow field. As a result of this, laminar sublayer beneath the absorber plate will get disturbed and this helps to increase the turbulence level of the air. This results in increased heat transfer rate from the absorber plate. Paper discusses the influence of different shaped turbulators used by the various researchers in improving the thermal performance of air heaters. Design considerations, geometries used, flow conditions and their influence on turbulence, heat transfer rate, absorber temperature and thermo-hydraulic enhancement factor have been thoroughly discussed. Finally concluding remarks and the future scope for additional enhancement in the performance of solar air heater is proposed.